Laparoscopic Ventral Mesh Rectopexy: Functional Outcomes after Surgery - Ahmad, Nasir Zaheer; Stefan, Samuel; Adukia, Vidhi; Naqvi, Syed Abul Hassan; Khan, Jim (The Surgery Journal, 2018)
Aims Rectal prolapse is a debilitating and unpleasant condition adversely affecting the quality of life. Laparoscopic ventral mesh rectopexy (LVMR) is recognized as one of the treatment options. The aim of this study was to evaluate the functional outcomes after a standardized LVMR.Methods A cohort of patients who underwent LVMR from 2011 to 2015 were contacted and asked to fill questionnaires about their symptoms before and after the surgery. Three questionnaires based on measurement of Wexner fecal incontinence (WFI), obstructive defecation syndrome (ODS), and Birmingham Bowel and Urinary Symptom (BBUS) scores were used to assess the changes in postoperative functional outcomes. Some additional questions were also added to further assess bowel dysfunction.Results There were 58 female patients with a mean age of 62.74 ± 15.20 (26–86) years in this cohort. About 70% of the patients participated in the study and returned the filled questionnaires. There was a significant overall improvement across all three scores (WFI: p = 0.001, ODS: p = 0.001, and BBUS: p = 0.001). Some individual components in the scoring systems did not improve to patient's satisfaction. No perioperative complication or conversion to an open procedure was reported in this study. Three recurrences were seen in the redo cases.Conclusion LVMR is a promising way of dealing with rectal prolapse. A careful patient selection, appropriate preoperative workup, and a meticulous surgical technique undoubtedly transform the postoperative outcomes.
Keywords: rectum; prolapse; rectopexy